Clinical effects of subgingivally delivered achyranthes aspera gel in chronic periodontitis: A clinical and microbiological study - Neeharika R Soorgani; Himanshu Khashu; Richa Agrawal; Reny K Ninan; Sonu Peter; Nilesh Mukka (Wolters Kluwer Medknow Publications, 2023)
Introduction: Periodontitis is an inflammatory disease of microbial origin. Local drug delivery agents help reduce subgingival microflora. Achyranthes aspera is a medicinal herb with antimicrobial, antioxidant, anti-inflammatory, and wound-healing properties. Materials and Methods: A split-mouth study was conducted, in which 60 sites were included. Clinical parameters included measurements of probing depth (PD), gingival index, and clinical attachment level (CAL). Gingival crevicular fluid (GCF) samples were collected, followed by microbiological analysis of Porphyromonas Gingivalis. Clinical and microbiological parameters were recorded at baseline and after 3 months. Statistical analysis was done using the Statistical Package of Social Science (SPSS Version 22; Chicago Inc., USA). Result: At 3 months, Group A resulted in greater mean reductions in clinical parameters: PD (3.77) as compared to Group B (5.23), and also greater mean CAL gain (3.18) in group A as compared to Group B (5.16). Group A also showed a significant reduction in the number of sites harboring periodontopathogens as compared to Group B. Conclusion: A. aspera gel can be used as a nonsurgical local drug delivery agent in patients with chronic periodontitis as an effective adjunct to SRP.